2016
DOI: 10.1080/09602011.2016.1214604
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioural assessment and diagnosis in disorders of consciousness: a preliminary study of the Sensory Tool to Assess Responsiveness (STAR)

Abstract: The Sensory Tool to Assess Responsiveness (STAR) is an interdisciplinary neurobehavioural diagnostic tool for individuals with prolonged disorders of consciousness. It utilises current diagnostic criteria and is intended to improve upon the high misdiagnosis rate in this population. This study assesses the inter-rater reliability of the STAR and its diagnostic validity in comparison with the Coma Recovery Scale-Revised (CRS-R) and the Wessex Head Injury Matrix (WHIM). Participants were patients with severe acq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The diagnosis of DOCs is largely based on behavioral responses to commands. Numerous clinical scales have been developed in Europe and the USA to help assess the levels of wakefulness and awareness before a diagnosis can be confirmed, including the Coma Recovery Scale-Revised (CRS-R) [8], Glasgow Coma Scale [9], Sensory Modality Assessment and Rehabilitation Technique [10], Wessex Head Injury Matrix [11], Reuth DOC Response Assessment [12], Sensory Tool to Assess Responsiveness [13], and Motor Behavior Tool [14]. Among these, the CRS-R is the most widely used standardized tool that includes the diagnostic criteria for coma, VS/UWS, and MCS and is based on the presence or absence of behavioral responses to specific sensory stimuli.…”
Section: Diagnosis and Prognosis Diagnosismentioning
confidence: 99%
“…The diagnosis of DOCs is largely based on behavioral responses to commands. Numerous clinical scales have been developed in Europe and the USA to help assess the levels of wakefulness and awareness before a diagnosis can be confirmed, including the Coma Recovery Scale-Revised (CRS-R) [8], Glasgow Coma Scale [9], Sensory Modality Assessment and Rehabilitation Technique [10], Wessex Head Injury Matrix [11], Reuth DOC Response Assessment [12], Sensory Tool to Assess Responsiveness [13], and Motor Behavior Tool [14]. Among these, the CRS-R is the most widely used standardized tool that includes the diagnostic criteria for coma, VS/UWS, and MCS and is based on the presence or absence of behavioral responses to specific sensory stimuli.…”
Section: Diagnosis and Prognosis Diagnosismentioning
confidence: 99%
“…Participants were given the option to indicate other formal assessments used in their setting. The Sensory Tool to Assess Responsiveness (STAR) (Stokes et al, 2018) and Music Therapy Assessment Tool for Awareness in Disorders of Consciousness (MATADOC) (Magee et al, 2014) were also used to determine emergence by 16.7% (n=6).…”
Section: Formal Assessmentmentioning
confidence: 99%
“…While there is arousal but no awareness in UWS, MCS shows fluctuating but reproducible signs of consciousness but an absence of reliable communication (Giacino et al, 2002). Plenty of studies have been carried out and several methods have been developed to differentiate the different states, like The Sensory Modality Assessment and Rehabilitation Technique (SMART) (Gill-Thwaites, 1997), The Wessex Head Injury Matrix (WHIM) (Shiel et al, 2000), the Sensory Tool to Assess Responsiveness (STAR) (Stokes et al, 2018), the Glasgow Coma Scale (GCS) (Teasdale and Jennett, 1972), the COMA/Near Coma Scale (CNC) (Rappaport et al, 2006), the Glasgow Outcome Scale (GOS) (Teasdale and Jennett, 1972), and the Coma Recovery Scale-Revised (CRS-R).…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, the activation of the auditory cortex is compared with the patient’s state of consciousness and it is concluded that the retention of the auditory cortex may be an indicator of the retention of consciousness (Heine et al, 2015). Tests based on auditory stimulation like auditory startle and localization to sound in CRS-R (American Congress of Rehabilitation Medicine et al, 2010) play an important role and more auditory stimulations have been used on other subjects (Teasdale and Jennett, 1972; Gill-Thwaites, 1997; Shiel et al, 2000; Stokes et al, 2018). Auditory stimulation is also effective in the recovery of consciousness, and a recent study focusing on the impact of sensory stimulation programs (SSP) in the recovery of DOC highlighted that SSP may not be sufficient to restore consciousness but it may lead to improved behavioral responsiveness in MCS patients (Cheng et al, 2018).…”
Section: Introductionmentioning
confidence: 99%